2014
DOI: 10.1155/2014/254396
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals and Antioxidant Status in Protein Energy Malnutrition

Abstract: Background/Objectives. The aim of this study was to evaluate oxidant and antioxidant status in children with different grades of Protein Energy Malnutrition (PEM). Subjects/Methods. A total of two hundred fifty (250) children (age range: 6 months to 5 years) living in eastern UP, India, were recruited. One hundred and ninety-three (193) of these children had different grades of PEM (sixty-five (65) children belong to mild, sixty (60) to moderate, and sixty-eight (68) to severe group). Grading in group was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 18 publications
3
34
0
3
Order By: Relevance
“…Loss of membrane integrity, in case of mitochondria, undermine the efficiency with which the electron transport chain converts reducing equivalents to ATP, thus further aggravating the adverse effect of already reduced energy intake in malnourished children. The high levels of MDA are in agreement with those of other studies carried out by Khare Perampalli, Bosnak and Ghone et al [6][7][8] Catal F et al and Anuradha J et al reported that significantly increased level of serum MDA in patients with malnutrition as compared to controls. 9,10 In such condition, depletion of endogenous antioxidants may be expected.…”
Section: Discussionsupporting
confidence: 91%
“…Loss of membrane integrity, in case of mitochondria, undermine the efficiency with which the electron transport chain converts reducing equivalents to ATP, thus further aggravating the adverse effect of already reduced energy intake in malnourished children. The high levels of MDA are in agreement with those of other studies carried out by Khare Perampalli, Bosnak and Ghone et al [6][7][8] Catal F et al and Anuradha J et al reported that significantly increased level of serum MDA in patients with malnutrition as compared to controls. 9,10 In such condition, depletion of endogenous antioxidants may be expected.…”
Section: Discussionsupporting
confidence: 91%
“…20 Furthermore, a dietary deficiency of protein and calories reduces the synthesis of antioxidant enzymes and antioxidant concentrations, leading to ROS overproduction. 19,21 Due to the financial costs involved in frequent audiological assessment or therapeutic drug monitoring (i.e., daily blood tests for AG concentration), early detection of hearing loss is impractical in most sub-Saharan African countries, which leads to missed opportunities to prevent hearing loss. 1,22 …”
Section: Introductionmentioning
confidence: 99%
“…The ability of the studied biomarkers to predict the need for PICU admission among patients with initially mild cases of sepsis still needs to be addressed. We also think that the behavior of these biomarkers should further be explored in cases of sepsis affecting patients with chronic metabolic or nutritional conditions, who may have a diminished capacity to deal with an additional oxidative injury [32].…”
Section: Discussionmentioning
confidence: 99%